Renal Artery Stenosis: A Unique Disease or a Broad Spectrum of Different Diseases? - Zuccala, Alessandro; Losinno, Francesco; Lifrieri, Francesca; Nicolo, Pierpaolo D. (Current Hypertension Reviews, 2007)
Renal ischaemia due to renal artery stenosis (RAS) may be the cause of end-stage renal failure in a growing number of patients. In recent years, decisions taken on the optimal management of patients with renal artery stenosis have sparked controversy and debate among cardiologists, internists and nephrologists. The main reason underlying the ongoing controversy may be the heterogeneity of clinical entities that are normally grouped together through the use of the umbrella term renal artery stenosis. Actually, when thinking of renal artery stenosis our view is still deeply shaped by Goldblatt's seminal study. Yet it should be remembered that in Goldblatt's experiment renal artery clipping occurred in the context of a perfectly healthy vascular tree. A clinical situation that comes close to Goldblatt's experiment is the one in which the stenosis mainly, if not exclusively, affects the renal artery in relatively young subjects whose vascular tree is not badly damaged. In clinical practice, this situation is frequently encountered in subjects bearing fibromuscular dysplasia (FMD), non-ostial or truncal stenosis (Tru-RAS), and stenosis of the transplanted kidney (TRAS). Contrariwise, ostial stenosis is more precisely a lesion of the thickened aortic wall that encroaches upon the renal artery ostium, rather than a lesion in the renal artery itself. Hence, the reference paradigm ought not to be Goldblatt's model but rather more complex models in which the narrowing of the renal artery is associated to other factors, such as a high cholesterol diet, smoking or aging. The causes of renal impairment are likely to be different in the two situations. In pure renal artery stenosis (FMD, TruRAS, TRAS), the decrease in GFR is mainly caused by hypoperfusion secondary to stenosis, which is then reversible after revascularization, while in subjects with ostial stenosis and/or in older subjects with a badly injured aorta the pathogenesis is multifactorial, with intrarenal atheroma, cholesterol embolism and ischaemic damage all making a contribution. This may account for the lack of correlation between the degree of stenosis and the entity of renal impairment, as well as the low rate of renal function recovery in subjects with ostial stenosis. In our view, keeping the different entities separate enables clinicians to take the right decision on revascularization.
Keywords: Renal artery stenosis